Acute assessment of microvascular perfusion patterns by myocardial contrast echocardiography during myocardial infarction: relation to timing and extent of functional recovery. Issue 1 (1st January 1999) - Czitrom, D; Karila-Cohen, D; Brochet, E; Juliard, J M; Faraggi, M; Aumont, M-C; Assayag, P; Steg, P G
Abstract : Objective: To examine the relation between the initial microvascular perfusion pattern, as assessed by intracoronary myocardial contrast echocardiography (MCE), immediately after restoration of TIMI (thrombolysis in myocardial infarction) (TIMI) grade 3 flow during acute myocardial infarction, and the extent and timing of functional recovery in the area at risk. Setting: Referral centre for interventional cardiology. Methods: Intracoronary MCE was performed 15 minutes after TIMI grade 3 recanalisation of the infarct artery in 25 patients. Segmental myocardial contrast patterns were graded semiquantitatively (0, none; 0.5, heterogeneous; 1, homogeneous). Functional recovery was assessed by echocardiography on days 9 and 42. Results: Among 174 myocardial segments in the area at risk, wall motion recovery on day 9 was observed in 40% of MCE grade 1 segments but there was no significant recovery in grade 0 or 0.5 segments. On day 42, recovery had occurred in 56% of MCE grade 1 segments (p < 0.0001 v MCE grade 0 and 0.5; p = 0.0001 v MCE grade 1 on day 9), and 22% of MCE grade 0.5 segments (p = 0.02 v MCE grade 0; p = 0.0005 v MCE grade 0.5 on day 9); MCE grade 0 segments did not recover. Negative predictive value in predicting recovery by contrast enhancement was 95% and 89% by days 9 and 42, respectively. Conclusions: Contractile recovery occurs earliest in well reperfused segments. Up to one quarter of segments with heterogeneous contrast enhancement show wall motion recovery within the first six weeks. Myocardial perfusion after recanalisation in acute myocardial infarction, even if heterogeneous, is a prerequisite for postischaemic functional recovery. Thus preservation of acute myocardial perfusion is associated with more complete and early functional recovery.